An Optimized Single Warehouse Inventory Model for Decaying ‎Goods with Time and Price Dependent Demand and Time Dependent Holding Cost Using the ABC Algorithm - Abid , Mohammed; Yadav , Ajay Singh; Viswanathan, Bhavani; Shivani (International Journal of Basic and Applied Sciences, 2025)
This paper presents a single-warehouse inventory model for items subject to deterioration, where shortages are fully backlogged. The model ‎considers a demand rate that is dependent on both time and selling price, while the holding cost is assumed to be a linear function of time. ‎To enhance the practical applicability of the model, deterioration and shortage costs are also included in the total cost function. The main ‎objective is to minimize the total inventory cost by determining the optimal cycle length and selling price. The Artificial Bee Colony (ABC) ‎algorithm, a nature-inspired metaheuristic, is applied to efficiently solve the nonlinear optimization problem associated with the model. A ‎numerical example illustrates the effectiveness of the proposed approach, and a sensitivity analysis is conducted to examine the impact of ‎key parameters on the total cost. The results demonstrate that the ABC algorithm performs robustly under varying conditions and provides a ‎reliable tool for optimizing inventory decisions involving deteriorating items‎.
Keywords: Inventory Model; Deteriorating Items; Time and Price Dependent Demand; Time-Dependent Holding Cost; Complete Backlogging; Artificial ‎Bee Colony Algorithm; Optimization; Sensitivity Analysis